A small town : a novel - Perry, Thomas, 1947- (The Mysterious Press, 2020)
"In A Small Town, twelve conspirators meticulously plan to throw open all the gates to the prison that contains them, so that more than a thousand convicts may escape and pour into the nearby small town. The newly freed prisoners rape, murder, and destroy the town-burning down homes and businesses. An immense manhunt ensues, but the twelve who plotted it all get away. After two years, all efforts by the local and federal police agencies have been in vain. The mayor and city attorney meet, and Leah Hawkins, a six-foot, two-inch former star basketball player and resident good cop, is placed on sabbatical so that she can tour the country learning advanced police procedures. The sabbatical is merely a ruse, however, as her real job is to track the infamous twelve. And kill them. Leah's mission takes her across the country, from Florida to New York, from California to an anti-government settlement deep in the Ozarks. Soon, the surviving fugitives realize what she is up to, and a race to kill or be killed ensues. Full of exhilarating twists and surprisingly resonant, A Small Town will sweep readers along on Leah's quest for vengeance"--